An Instructional Design For The Teaching Of English AtSMP Negeri 14 Surakarta In 2013/2014 Academic Year:A Naturalistic Study - Megawati, Gayuh; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
The study is aimed at observing the instructional design for the teaching of English at SMP Negeri 14 Surakarta in 2013/1014 academic year. The objective of study is to describe the instructional design for the teaching of English at SMP Negeri 14 Surakarta. In this research, there are nine component of instructional design, namely: (1) Learning Objective. (2) Syllabus. (3) Instructional Material. (4) The Classroom Procedure. (5) Technique in Teaching English. (6) Teacher's Role. (7) Learner's Role. (8) Teaching Media. (9) Evaluation Model. The type of the study is descriptive qualitative especially naturalistic approach. In this research, the data are derived from event, informant, and field note. There are three techniques of collecting data, namely: observation, interview, and analyzing document. Methods of Analyzing data are reduction the data, display the data, and conclusion or verification. The techniques of analyzing data are reduction of data, display the data, and verification or drawing conclusion. The result of the study is: (1) There are two learning objectives of teaching English especially in English teaching namely: general objective and specific objective. In general learning objective based on KTSP curriculum. In specific learning objective of teaching English is written in syllabus and it supported indicator of lesson plan.(2) The type of syllabus is notional functional syllabus.(3) The instructional material used is printed material and the material that compare both print and non print source as sell access material and material on the internet.(4) the classroom procedure used is 5E (Engagement, Exploration, Explanation, Elaboration and Evaluation) with different patterns.(5) Techniques used in teaching English are reading a passage, skimming and scanning a passage, brainstorming, discussing a topic or question, peer-editing.(6) The teacher's role are facilitator, observer, organizer, explainer.(7) the learner's role are monitor and evaluation their progress, learner learn from the teacher, members of a group and learn by interacting with others.(8) The media used in teaching learning process is textbook as printed media and LCD projectors as electric media.(9) Evaluation models used are daily examination, middle text and final test.